Constitutional hemeneutics: The art of interpreting - Madeira , Fernando Nunes; de Andrade, Maxwel Mota (Seven Editora, 2024)
This article explores the concept, forms, and challenges of constitutional hermeneutics, highlighting its importance for the realization of fundamental values and principles. The different interpretative approaches are presented, such as literal, historical, teleological, systematic, according to the Constitution, evolutionary and pluralist. The methodology adopted was the literature review. The results show that constitutional interpretation is a complex activity, requiring from the interpreter not only legal knowledge, but also sensitivity, creativity and ethical commitment. It is concluded that constitutional hermeneutics is an essential science and art for the construction of a democratic and just society, guided by the ideals of freedom, equality and human dignity, allowing the interpreter to act as guardian of the Constitution and transforming agent of social reality. DOI:https://doi.org/10.56238/sevened2024.026-015